The Effect of Transfers and Position Promotions on Employee Performance with Career Development as an Intervening Variable for BPJS Employment Medan Raya - Dora Oktaviana; Kiki Farida Ferine (International Journal of Economics, Management and Accounting (IJEMA), 2023)
In this study, the researcher wanted to see the effect of Transfers and Position Promotions on Employee Performance with Career Development as Intervening Variables. This research used associative quantitative research. research of all populations so that researchers used saturated sample techniques. This study uses the Smart PLS device to calculate the results of this study. This research model uses Path analysis. Based on the results of the research that has been carried out and the data analysis as explained in the previous chapter, the following conclusions are conveyed from the results of the research as follows: Mutations have a positive and significant effect on employee performance. Mutations have a positive and significant effect on Career Development. Career Development has no significant positive effect on Employee Performance. Position Promotion has a positive and significant effect on Employee Performance. Promotion has a positive and significant effect on Career Development. Mutations have a positive and insignificant effect on Employee Performance through Career Development with. Promotion has no significant positive effect on Employee Performance through Career Development.